Intercultural management competence in Finnish multicultural working life : case Aamujakelu Oy - Metsä-Ketelä, Johanna (2010)
The current thesis is a qualitative case study, which explores intercultural management competence in Finnish working life. The subject is investigated from the viewpoint of the Finnish supervisors and the international employees at a Finnish multicultural workplace. The aim of the thesis is to determine what kind of intercultural management competence the supervisors of the case company need in their daily work.